Time and space in long-term development of agriculture and rural areas – a retrospective approach - Marek Wigier (Journal of Agribusiness and Rural Development, 2012)
The development processes taking place in agriculture and rural areas have a causal relationship with time and the socio-economic space to which they belong. The subject of this discussion is an attempt to systematize some achievements of science relating to the above mentioned areas through the prism of the theory of location of economic activity in agriculture, welfare economics and neoclassical models of growth and conver-gence, and models of agricultural development worldwide, with an indication of the rela-tionship between the industrial agriculture, space and sustainable development. It is also an attempt to present the relationship: the farming – the rural areas – the environment, in the context of an active agricultural policy and spatial policy.